A systematic review for switchgear asset management in power grids: condition monitoring, health assessment, and maintenance strategy - Zhou, Nan (2023)
Asset management process and techniques can improve the cost-efficiency, balance the cost and risk, and prolong the service life of the aging switchgears in power grids, which have become increasingly important for electric utilities. This paper provides an insight into the recent developments in switchgear asset management and explore future research stream. Accordingly, three directions: condition monitoring, health assessment, and maintenance strategy have been addressed. We first present switchgear condition monitoring indicators and condition evaluation methods utilizing these condition data. Subsequently, we explain health index methodologies to achieve switchgear health assessment and remaining useful life estimation. With these results, we then present the maintenance strategy and life cycle cost optimization methods to address cost-efficient decision making. Finally, the limitation of existing methods and future research trend are discussed. This paper covers various asset management domains, attempting to create a common understanding and fill the gaps among the academic, industry, and technology area.